2010
DOI: 10.1016/j.cell.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Fibroblasts into Functional Cardiomyocytes by Defined Factors

Abstract: SUMMARY The reprogramming of fibroblasts to induced pluripotent stem (iPS) cells raises the possibility that a somatic cell could be reprogrammed to an alternative differentiated fate without first becoming a stem/progenitor cell. A large pool of fibroblasts exists in the post-natal heart, yet no single “master regulator” of direct cardiac reprogramming has been identified. Here, we report that a combination of three developmental transcription factors (i.e., Gata4, Mef2c and Tbx5) rapidly and efficiently repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
2,193
11
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,268 publications
(2,271 citation statements)
references
References 40 publications
46
2,193
11
21
Order By: Relevance
“…Together with Baf60 and Gata4, Tbx5 induces the formation of ectopic cardiomyocytes in mouse embryonic mesoderm (Takeuchi and Bruneau, 2009) and, as shown recently, the transduction of Tbx5, Mef2c, and Gata4 into cardiac fibroblasts leads to the stimulation of cardiomyocyte formation (Ieda et al, 2010), indicating the importance of Tbx5 for cardiogenesis. Until now, there were no data available analyzing Tbx5 function with respect to the novel concept of two separate cardiac lineages derived from a common precursor cell population.…”
Section: Introductionsupporting
confidence: 56%
“…Together with Baf60 and Gata4, Tbx5 induces the formation of ectopic cardiomyocytes in mouse embryonic mesoderm (Takeuchi and Bruneau, 2009) and, as shown recently, the transduction of Tbx5, Mef2c, and Gata4 into cardiac fibroblasts leads to the stimulation of cardiomyocyte formation (Ieda et al, 2010), indicating the importance of Tbx5 for cardiogenesis. Until now, there were no data available analyzing Tbx5 function with respect to the novel concept of two separate cardiac lineages derived from a common precursor cell population.…”
Section: Introductionsupporting
confidence: 56%
“…The characterization of blastema cell surface antigen and micro-RNAs will also be important. Might it be possible to directly reprogram dermal fibroblasts in situ to limb cell types other than cartilage, for example muscle, as has been reported for the reprogramming of mammalian neonatal cardiac fibroblasts into functional cardiomyocytes (Ieda et al, 2010)? This would be valuable as a therapy to reconstitute individual limb tissues damaged by injury.…”
Section: Mechanisms Of Histolysis and Dedifferentiationmentioning
confidence: 99%
“…Takeuchi and Bruneau (2009) show that GATA4 acts together with Tbx5 and Baf60c to direct ectopic differentiation of mouse mesoderm into beating cardiomyocytes. And more recently Ieda et al (2010) have reported that GATA4 is among a combination of three developmental transcription factors (i.e., with Mef2c and Tbx5) that rapidly and efficiently reprogramme post-natal cardiac or dermal fibroblasts directly into differentiated cardiomyocyte-like cells.…”
Section: Differential Requirements For Gata Factors Are Mediated By Nmentioning
confidence: 99%
“…Recent studies in mouse have confirmed the importance of this factor and show that GATA4 is among three factors (GATA4, Tbx5, and Baf60c) that together are sufficient for transdifferentiation of non-cardiogenic mesoderm into beating cardiomyocytes (Takeuchi and Bruneau, 2009). In addition, GATA4 together with Mef2c and Tbx5 is able to reprogram postnatal cardiac or dermal fibroblasts directly into differentiated cardiomyocytes-like-cells (Ieda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%